If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 6B = -72 Solving 18 + 6B = -72 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6B = -72 + -18 Combine like terms: 18 + -18 = 0 0 + 6B = -72 + -18 6B = -72 + -18 Combine like terms: -72 + -18 = -90 6B = -90 Divide each side by '6'. B = -15 Simplifying B = -15
| 5p+1=2.2 | | 6y-4=2x-8 | | (6x+8)+(-7x-11)= | | 4p+3=.8 | | 4(4/5)+4(-9/5)=-4 | | (x+4)/(4)=(x)/(x-2) | | 9-12+5= | | cx-y=2 | | (x-3)-9=0 | | 9p+5.8= | | 4(4/5)-(-9/5)=5 | | 7x+9y-6x-11y= | | 60x-60x^3=0 | | 9p+4=5.8 | | 9--12+5= | | 2x-((3x^2)/36) | | 9/4y=2/3y | | 5y+2=4.5 | | -7+2x-5x=-7 | | y=4(4/5)-5 | | 6-3(x+2)=12 | | -6a-a= | | 2k+3=5.4 | | 36t^2/3+36t^1/3+9=0 | | -1/5(n+2)=10 | | 2k+5.4=3 | | 114/14 | | -1.5(n+2)=10 | | 2x^2+4=4x^2-8x+4 | | 49/98=8/12 | | 3k+2=5.4 | | (2+-6)=-24 |